1984
DOI: 10.1007/bf00216529
|View full text |Cite
|
Sign up to set email alerts
|

Responses of the PAS-positive pars intermedia cells in the cichlid fish Sarotherodon mossambicus to ambient calcium and background adaptation

Abstract: Please be advised that this information was generated on 2018-05-09 and may be subject to change.Cell Tissue Res (1984) Summary. The function of the PAS-positive pars intermedia cells in fish has been connected with control of background adaptation and of plasma calcium levels. Since background reflectivity and illumination influence calcium metabolism in S. mossambicus, we have tested the hypothesis that the effects of background reflectivity on the PAS-positive cells are mediated by changes in plasma calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1984
1984
1988
1988

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Such responses are not con sistently found in PIPAS cells. For the cichlid fish Oreochromis mossambicus we have shown that these cells do not respond to alLnges in external or internal calcium concen trations and we have concluded that in this species the PIPAS cells are unlikely to be involved in the endocrine control of calcium emtabolism (Van Eys and Wendelaar Bonga 1984). The present data on goldfish support this conclusion.…”
Section: / Pi Pas Cells and Calciumsupporting
confidence: 67%
See 1 more Smart Citation
“…Such responses are not con sistently found in PIPAS cells. For the cichlid fish Oreochromis mossambicus we have shown that these cells do not respond to alLnges in external or internal calcium concen trations and we have concluded that in this species the PIPAS cells are unlikely to be involved in the endocrine control of calcium emtabolism (Van Eys and Wendelaar Bonga 1984). The present data on goldfish support this conclusion.…”
Section: / Pi Pas Cells and Calciumsupporting
confidence: 67%
“…PIPAS cells are exclusively found in teleosts (Ball and Batten 1981). Their function is still in dispute (Ball and Batten 1981;Pang 1981;Ball et al 1982;Olivereau et al 1982a, b;Van Eys and Wendelaar Bonga 1984). In some fish species these cells respond to changes in osmolar ity of the ambient water, or to changes in background re flectivity (Ball and Batten 1981;Van Eys 1980).…”
mentioning
confidence: 99%